Comparison of Prostate Biopsy with or without Prebiopsy Multiparametric Magnetic Resonance Imaging for Prostate Cancer Detection: An Observational Cohort Study - Bryant, Richard J; Hobbs, Catherine P; Eyre, Katie S; Davies, Lucy C; Sullivan, Mark E; Shields, William; Sooriakumaran, Prasanna; Verrill, Clare L; Gleeson, Fergus V; MacPherson, Ruth E; Hamdy, Freddie C; Brewster, Simon F (The Journal of urology, 2019)
We hypothesized that 1) introducing prebiopsy multiparametric magnetic resonance imaging would increase the diagnostic yield of transrectal prostate biopsy and 2) this would inform recommendations regarding systematic transrectal prostate biopsy in the setting of negative prebiopsy multiparametric magnetic resonance imaging. A total of 997 biopsy naïve patients underwent transrectal prostate biopsy alone to June 2016 (cohort 1) and thereafter 792 underwent transrectal prostate biopsy following prebiopsy multiparametric magnetic resonance imaging (cohort 2). Patients with lesions on prebiopsy multiparametric magnetic resonance imaging underwent cognitive targeted plus systematic transrectal prostate biopsy. Patients without lesions underwent systematic transrectal prostate biopsy. Cohort 2 comprised younger men (age 68 vs 69 years, p = 0.01) with lower prostate specific antigen (7.6 vs 7.9 ng/ml, p = 0.024) and smaller prostate volume (56.1 vs 62 cc, p = 0.006). In cohort 2 vs cohort 1 there was no increase in overall prostate cancer detection (57.6% vs 56.7%, p = 0.701), the Gleason Grade Group or the number of positive cores (each p >0.05). Increased multifocal prostatic intraepithelial neoplasia, maximum prostate cancer core length (5 mm or greater vs less than 5 mm) and radical surgery/high intensity focused ultrasound (each p <0.05) were observed in cohort 2. For Gleason Grade Group 2-5 prostate cancer negative prebiopsy multiparametric magnetic resonance imaging had 88.1% sensitivity, 59.8% specificity, 67.8% positive predictive value and 84% negative predictive value. For negative prebiopsy multiparametric magnetic resonance images a prostate specific antigen density cutoff of 0.15 ng/ml or greater increased clinically significant prostate cancer detection only if the latter was defined as Gleason Grade Group 3-5 disease and/or tumor length 6 mm or greater. Introducing prebiopsy multiparametric magnetic resonance imaging in our clinical setting increased the diagnostic yield of prostate cancer per biopsy core. Not performing a systematic transrectal prostate biopsy when prebiopsy multiparametric magnetic resonance imaging was negative would have led to under detection of 15.1% of Gleason Grade Group 2 or greater prostate cancer cases (approximately 1 in 6).